Experimental analysis on the efficacy of water-based mud containing modified graphene nanoplatelets in transporting sand particles through concentric and eccentric drill pipes - Muftahu Nuhu Yahya; Muhammad Nurul Anam Bin Mohd Norddin; Azad Anugerah Ali Rasol; Jeffrey Oseh; Muhammad Muhammad; Ahmed Rafiq Albajalan (Arabian Journal of Geosciences, 2026)
Traditional drilling muds frequently have trouble efficiently transporting cuttings to the surface, which impedes drilling efficiency and progress. The possibility of a nano addition to enhance the cutting transport capability of water-based muds (WBM) is examined in this work. This study employed graphene nanoplatelets (GNPs)-based drilling muds made from rice husk waste and modified with Triton-X100 to determine how sandstone particles are removed from vertical and deviated pipelines at 0 o , 50 o , 55 o , and 60 o . This study primarily focused on how the mud velocity of modified GNPs (GR-T) and unmodified GNPs (GR) at 0.125, 0.25, and 0.375wt.% concentrations affected WBM cutting transport efficiency (CTE). To solve this problem, a tailor-made flow loop was constructed to simulate vertical and deviated well conditions at 0.6, 0.8, and 1.0 L/s mud flowrates. Furthermore, sandstone particles from 1.40 to 2.00 mm were selected to replicate drilled cuttings at varied pipe eccentricities (e = -1, 0, and + 1). The results show that GR-T concentrations are more stable and effective than GR concentrations at improving rheology, filtration, and removal of sandstone particles in the WBM system. In all experiments, the vertical (0°) pipe angle is easiest to clean, whereas the 55° angle is hardest. An eccentric drill pipe (e = + 1) cleaned the solid particles the most. The CTE of the GR-T mud system was 52% at e = -1, 55% at e = 0, and 57% at e = + 1 at a hole angle of 55◦. The removal of cuttings was facilitated at higher mud flow rates, as the increased agitation enhanced mud velocity, altered the conveyance of cuttings within the downstream flow, promoted their transition to the upstream flow, and consequently inhibited the development of a cuttings bed. Due to lesser mud velocity, removal of bedding formation was less effective at lower flowrates. The study found that higher mud rheology and flowrates erode sandstone particles the most. Additionally, the examined GR-T induced sufficient mud velocity to significantly influence the positive eccentric annulus, which improved the WBM cutting transport capacity and expedited deviated wellbore drilling.